Update on newborn dried bloodspot testing for cerebrotendinous xanthomatosis: An available high-throughput liquid-chromatography tandem mass spectrometry method - Bleyle, Lisa (Mol Genet Metab Rep, 2016)
BACKGROUND: Cerebrotendinous xanthomatosis (CTX) is a rare genetic disorder of bile acid synthesis that can cause progressive neurological damage and premature death. Detection of CTX in the newborn period would be beneficial since an effective treatment is available. We previously described a liquid chromatography-electrospray ionization-tandem mass spectrometry (LC-ESI-MS/MS) test with potential to screen newborn dried bloodspots (DBS) for CTX. We report here modifications to the methodology and application of the modified test to analysis of DBS from a CTX-affected and unaffected newborns. METHODS: The testing methodology utilizes keto derivatization to enable sensitive LC-ESI-MS/MS measurement of elevated 7α,12α-dihydroxy-4-cholesten-3-one (7α12αC4) in CTX newborn DBS. We report here method modifications, including use of a DBS extraction procedure used in newborn screening laboratories and a reduced analysis time of 2 min per sample. RESULTS: Rapid isotope-dilution LC-ESI/MS/MS quantification of the ketosterol bile acid precursor 7α12αC4 provides a test that could readily discriminate a CTX positive newborn DBS sample (with a concentration of 104.4 ng/ml) from unaffected newborn samples (with a mean concentration of 4.1 ± 3.4 ng/ml; range 0.2–15.6 ng/ml, n = 39) analyzed in a blinded manner. CONCLUSIONS: We provide additional evidence suggesting 7α12αC4 may be a promising test marker to screen newborn DBS for CTX. Early detection and intervention through newborn screening would greatly benefit those affected with CTX, preventing morbidity and mortality.